Co-CFA-1-based butadiene polymerization catalyst as well as preparation and application thereof
By using a butadiene polymerization catalyst based on Co-CFA-1, the problems of low yield and high side reactions of the butadiene polymerization catalyst in the prior art are solved, and the preparation of high-quality polybutadiene products with high cis structure, high molecular weight and narrow molecular weight distribution are realized.
Patent Information
- Application Number
- CN202411839807.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The prior art has problems such as low yield and many side reactions in butadiene polymerization catalysts, and it is difficult to effectively promote the synthesis of butadiene.
A butadiene polymerization catalyst based on Co-CFA-1 is used, which includes Co-CFA-1, a co-catalyst and a toluene solvent. The molar ratio of aluminum element in the co-catalyst and cobalt element in Co-CFA-1 is 20 to 300:1. The catalytic activity and cis structure content are improved through specific preparation methods and activation conditions.
High-quality polybutadiene products with high cis structure, high molecular weight and narrow molecular weight distribution are achieved, with high yield and few side reactions, and the catalyst has wear resistance and high tensile strength.
Smart Images

Figure HDA0005187684470000011
Abstract
Description
Technical Field
[0001] The invention relates to a butadiene polymerization catalyst based on Co-CFA-1 and a preparation method and application thereof. Technical Background
[0002] Butadiene rubber (BR), full name cis-1,4 polybutadiene rubber, molecular formula is (C4H6) n It is a kind of synthetic rubber with regular structure made by polymerization of butadiene. Its molecular chain is mainly composed of cis-1,4-structural units. Butadiene rubber is a general synthetic rubber, which is synthesized with butadiene as monomer and different catalysts and polymerization methods.
[0003] The production process of butadiene rubber uses different catalyst systems and formulations such as nickel, titanium, cobalt, lithium, and rare earth neodymium. These different catalyst systems and formulations are the key to butadiene rubber production, and they determine the microstructure of the polymer and the properties of the rubber.
[0004] Butadiene is an important organic chemical raw material, widely used in the production of synthetic rubber, plastics, nylon and other polymer materials. With the continuous development of industrial technology, higher requirements are put forward for the yield, purity and production efficiency of butadiene polymerization. Therefore, the optimization and innovation of butadiene experiments have important practical significance and economic value.
[0005] In recent years, metal-organic frameworks (MOFs) are a rapidly developing type of coordination polymers. MOFs have a unique three-dimensional pore structure and have received extensive attention in the field of single-site heterogeneous catalysis. MOFs materials have shown unique advantages in the field of heterogeneous catalysis due to their single dispersion and specific transition metal coordination environment. Secondly, secondary building units (SBUs) can realize the exchange of small molecules such as transition metals on solid supports. Many SBUs can also change their local coordination structure through cation exchange to achieve the regulation of their coordination configuration.
[0006] In the butadiene experiment, we used a new catalyst that has high activity and selectivity and can effectively promote the synthesis reaction of butadiene. Compared with traditional catalysts, the new catalyst has significant advantages in improving yield and reducing side reactions.
[0007] Metzger ED, Comito RJ, WU Z, et al. Highly Selective Heterogeneous Ethylene Dimerization with a Scalable and Chemically Robust MOF Catalyst[J]. ACS Sustainable Chemistry&Engineering, 2019, 7(7): 6654-61. reported the effects of Co-MFU-4l and Ni-MFU-4l in ethylene polymerization via cation exchange, but these were less effective in butadiene polymerization.
[0008] CFA-1 (Zn5 (OAc) 4 (bibta) 3) is a rigid metal organic framework material with Zn as the metal center and H2BTDD as the organic ligand. It has good hydrothermal stability and chemical stability. SBU can also change its local coordination structure through cation exchange. Through ion exchange and coordination, Co ions can be exchanged to CFA-1 to obtain the cobalt-based catalyst Co-CFA-1. Cobalt-based catalysts have great potential for the preparation of high-quality polybutadiene rubber with high cis, high molecular weight and narrow molecular weight distribution. Summary of the invention
[0009] The purpose of the present invention is to provide a butadiene polymerization catalyst based on Co-CFA-1 and its preparation and application, wherein the catalyst has the characteristics of simple synthesis, high catalytic activity, high cis structure, etc., and realizes high-quality polybutadiene products with high cis structure, high molecular weight and narrow molecular weight distribution.
[0010] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0011] In a first aspect, the present invention provides a butadiene polymerization catalyst based on Co-CFA-1, the butadiene polymerization catalyst comprising Co-CFA-1, a co-catalyst and a toluene solvent, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 is 20 to 300:1;
[0012] The Co-CFA-1 is prepared by the following method: heating a NMF dispersion of CFA-1 and cobalt acetate tetrahydrate at 55-65° C. for 18-30 hours, filtering, washing, and vacuum drying to obtain Co-CFA-1;
[0013] The co-catalyst is composed of alkyl aluminum and methyl aluminoxane in a molar ratio of 2 to 5:1, and the alkyl aluminum is selected from at least one of diethyl aluminum monochloride, triisobutyl aluminum and ethyl aluminum dichloride.
[0014] Preferably, the feed mass ratio of CFA-1 to cobalt acetate tetrahydrate is 0.06-0.12:1.2-1.8; more preferably 0.07-0.10:1.3-1.7.
[0015] Preferably, the feed mass volume ratio of CFA-1 to NMF is 1 g: 350-420 mL.
[0016] Preferably, during the preparation of Co-CFA-1, methanol is used as the washing reagent.
[0017] Preferably, during the preparation of the Co-CFA-1, the vacuum drying is performed at 220-250°C.
[0018] Preferably, the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 is 100-300:1, more preferably 150-160:1.
[0019] Preferably, in the co-catalyst, the molar ratio of alkyl aluminum to methyl aluminoxane is 4:1.
[0020] Preferably, the alkylaluminum is diethylaluminum monochloride.
[0021] The most preferred butadiene polymerization catalyst of the present invention is that the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 is 150-160:1; the co-catalyst is composed of diethylaluminum monochloride and methylaluminoxane, and the molar ratio of diethylaluminum monochloride to methylaluminoxane is 4:1.
[0022] The CFA-1 in the present invention is a rigid metal organic framework material, which can be prepared by methods reported in the literature. The present invention specifically recommends the following method for preparation:
[0023] DMF and acetic acid are added to a polyfluoroethylene liner and mixed, and the mixture is stirred at room temperature for 10 to 20 minutes, Zn·2H2O and H2bibta (1H, 1'H-5,5'-bibenzo[d][1,2,3]triazole) are added thereto, and ultrasonic mixing is performed uniformly. The mixture is placed in an oven and reacted at 90° C. for 16 hours and at 120° C. for 18 to 24 hours, and the mixture is washed with DMF and isopropanol, and vacuum dried at 50 to 90° C. to obtain CFA-1; wherein the volume ratio of DMF to acetic acid is 22 to 28:0.8 to 1.2, preferably 24 to 26:0.8 to 1; and the mass volume ratio of Zn·2H2O to H2bibta is 3 to 3.6:0.8 to 1.2, preferably 3.3 to 3.6:0.8 to 1.
[0024] The present invention has no special requirements for the amount of solvent in the butadiene polymerization catalyst, as long as it can disperse Co-CFA-1 and the co-catalyst. In a specific embodiment of the present invention, the mass concentration of Co-CFA-1 in the catalyst is 4-6 g / L.
[0025] In a second aspect, the present invention provides a method for preparing a butadiene polymerization catalyst based on Co-CFA-1 according to the first aspect, the preparation method comprising:
[0026] (1) heating a NMF solution of CFA-1 and cobalt acetate tetrahydrate at 55-65° C. for 18-24 hours, filtering, washing, and vacuum drying to obtain Co-CFA-1;
[0027] (2) Add Co-CFA-1 to a clean, dry reaction vessel, first add a toluene solution of alkyl aluminum, then add a toluene solution of methylaluminoxane, and activate at 20 to 40° C. for 10 to 40 minutes to obtain a butadiene polymerization catalyst based on Co-CFA-1.
[0028] Preferably, in step (1), the mass ratio of CFA-1 to cobalt acetate tetrahydrate is 0.06-0.12:1.2-1.8, more preferably 0.07-0.10:1.3-1.7.
[0029] Preferably, in step (1), the mass volume ratio of CFA-1 to NMF is 1:350-420.
[0030] Preferably, in step (1), the washing reagent is methanol.
[0031] Preferably, in step (1), the vacuum drying is carried out at 220-250°C.
[0032] To further improve the efficiency of catalyst preparation, step (2) of the present invention can usually be carried out under the protection of an inert gas or under vacuum conditions. The present invention does not strictly limit the inert gas used, for example, more economical nitrogen (N2) can be selected. Preferably, step (2) is carried out under vacuum conditions, and the activation conditions are: 20-25°C for 20-30 minutes.
[0033] In a third aspect, the present invention provides use of the Co-CFA-1-based butadiene polymerization catalyst described in the first aspect in the preparation of cis-polybutadiene.
[0034] The application is specifically as follows: 1,3-butadiene monomer and a butadiene polymerization catalyst based on Co-CFA-1 are mixed in a solvent, and then a polymerization reaction is carried out to generate cis-polybutadiene, and the reaction process is carried out under vacuum conditions.
[0035] As further preferred, the solvent is toluene.
[0036] As a further preference, the butadiene polymerization process is carried out under the protection of an inert gas to further facilitate the activity of butadiene polymerization. The present invention does not strictly limit the inert gas used, for example, relatively economical nitrogen (N2) can be selected.
[0037] As a further preferred method, the amount of the butadiene polymerization catalyst based on Co-CFA-1 is controlled so that the molar ratio of the cobalt element to the 1,3-butadiene monomer is 5.0×10 -4 ~2.5×10 -3 .
[0038] As a further preference, the feed concentration of 1,3-butadiene in the polymerization reaction system is 1.5-3.5M.
[0039] As a further preference, the polymerization temperature is 20-50°C. Under the polymerization conditions of the present invention, the reaction speed is uniform, a higher cis structure can be achieved, and the polymerization is generally completed within 80-150 minutes. The molecular weight is 2.6×10 4 ~8.7×10 5 , and further preferably the polymerization reaction temperature is 21°C and the reaction time is 2.5h.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The Co-CFA-1-based butadiene polymerization catalyst provided by the present invention has the advantages of wear resistance, high tensile strength, high activity, etc., and can prepare high-quality polybutadiene rubber products with the characteristics of high cis-structure content, controllable molecular weight, narrow molecular weight distribution, etc., and the product has a high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a SEM image of Co-CFA-1 prepared in Example 1. DETAILED DESCRIPTION
[0043] The present invention is described below with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way. A person skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0044] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0045] Example 1
[0046] 1. Preparation of Catalyst
[0047] (1) Preparation of CFA-1
[0048] 100 mL of DMF was measured with a measuring cylinder and poured into a polyvinyl fluoride liner. 4 mL of acetic acid was added with a pipette, mixed, and stirred at room temperature for 10 min. Then 0.74 g of (CH3COO)2Zn·2H2O and 0.2 g of H2bibta were weighed into the above solution and ultrasonically mixed. The mixed solution was placed in a 250 mL reactor, sealed, and placed in an oven for reaction at 90°C for 16 h and 120°C for 24 h. After the sample was cooled to room temperature, it was filtered, washed three times with DMF and isopropanol respectively, and finally dried in a vacuum oven at 50°C for 24 h to obtain 0.3 g (0.24 mmol) of white CFA-1.
[0049] (2) Preparation of Co-CFA-1:
[0050] Weigh 1.64g of cobalt (II) acetate tetrahydrate into a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) into the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 into the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1. The SEM image of the product is shown in Figure 1 The mass percentage of Co calculated by EDS content is 13.88%, see Table 1 for details.
[0051] Table 1
[0052] element Wt% C 65.14 N 3.42 O 15.94 Co 13.88 Zn 1.63 Total amount: 100.00
[0053] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times, and then vacuumed. First, 0.9 mL (2 mol / L) of a toluene solution of diethylaluminum chloride was added, and then 0.3 ml (1.5 mol / L) of a toluene solution of methylaluminoxane was added for activation. The mixture was activated at 25° C. for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 154:1.
[0054] 2. Synthetic polydiene rubber
[0055] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0056] The yield of polybutadiene rubber was 91.2% by gravimetric determination, with stereoselectivity of 99.6% 1,4-cis, 0.22% 1,4-trans, 0.18% 1,2-vinyl, and Mn of 8.2×10 5 , Mw / Mn is 2.6.
[0057] Example 2 (Different amount of co-catalyst used from Example 1)
[0058] 1. Preparation of rare earth catalysts
[0059] (1) Preparation of CFA-1: Same as Example 1
[0060] (2) Preparation of Co-CFA-1:
[0061] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0062] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times. Then, evacuation was performed, and 1.5 mL (2 mol / L) of a toluene solution of diethylaluminum chloride was first added, followed by 0.5 ml (1.5 mol / L) of a toluene solution of methylaluminoxane for activation. The reaction was activated at 25° C. for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 257:1.
[0063] 2. Synthetic polydiene rubber
[0064] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0065] The yield of polybutadiene rubber was 89.8% by gravimetric determination, with stereoselectivity of 99.1% 1,4-cis, 0.58% 1,4-trans, 0.32% 1,2-vinyl, and Mn of 5.5 × 10 5 , Mw / Mn is 2.65.
[0066] Example 3 (different co-catalyst mixing ratio from that used in Example 1)
[0067] 1. Preparation of rare earth catalysts
[0068] (1) Preparation of CFA-1: Same as Example 1
[0069] (2) Preparation of Co-CFA-1:
[0070] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0071] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times. Then, evacuation was performed, and 0.6 mL (2 mol / L) of a toluene solution of diethylaluminum chloride was first added, followed by 0.2 ml (1.5 mol / L) of a toluene solution of methylaluminoxane for activation. The reaction was activated at 25° C. for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 103:1.
[0072] 2. Synthetic polydiene rubber
[0073] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0074] The yield of polybutadiene rubber was 86.8% by gravimetric determination, with stereoselectivity of 94.9% 1,4-cis, 3.89% 1,4-trans, 1.21% 1,2-vinyl and Mn of 9.6 × 10 4 , Mw / Mn is 3.3.
[0075] Example 4 (different activation time from that used in Example 1)
[0076] 1. Preparation of rare earth catalysts
[0077] (1) Preparation of CFA-1: Same as Example 1
[0078] (2) Preparation of Co-CFA-1:
[0079] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0080] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times, and then vacuumed. First, 0.9 mL (2 mol / L) of a toluene solution of diethylaluminum chloride was added, and then 0.3 ml (1.5 mol / L) of a toluene solution of methylaluminoxane was added for activation. The mixture was activated at 25° C. for 40 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 154:1.
[0081] 2. Synthetic polydiene rubber
[0082] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0083] The yield of polybutadiene rubber was 91.4% by gravimetric determination, with stereoselectivity of 97.9% 1,4-cis, 1.28% 1,4-trans, 0.82% 1,2-vinyl, and Mn of 1.8 × 10 5 , Mw / Mn is 2.82.
[0084] Example 5 (different type of co-catalyst used from Example 1)
[0085] 1. Preparation of rare earth catalysts
[0086] (1) Preparation of CFA-1: Same as Example 1
[0087] (2) Preparation of Co-CFA-1:
[0088] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0089] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times, and then vacuumed. 1.5 mL of methylaluminoxane toluene solution (1.5 mol / L) was added for activation, and the reaction was activated at 25°C for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 154:1.
[0090] 2. Synthetic polydiene rubber
[0091] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0092] The yield of polybutadiene rubber was 58.8% by gravimetric determination, with stereoselectivity of 85.6% 1,4-cis, 8.1% 1,4-trans, and 6.3% 1,2-vinyl, and Mn was 1.2 × 10 4 , Mw / Mn is 4.2.
[0093] Example 6 (different type of co-catalyst used from Example 1)
[0094] 1. Preparation of rare earth catalysts
[0095] (1) Preparation of CFA-1: Same as Example 1
[0096] (2) Preparation of Co-CFA-1:
[0097] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0098] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times, and then vacuumed. First, 0.7 mL (1.5 mol / L) of triisobutylaluminum toluene solution was added, and then 0.6 ml of diethylaluminum monochloride (2 mol / L) toluene solution was added for activation. The mixture was activated at 25°C for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 154:1.
[0099] 2. Synthetic polydiene rubber
[0100] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0101] The yield of polybutadiene rubber was 90.1% by gravimetric determination, with stereoselectivity of 91.56% 1,4-cis, 4.82% 1,4-trans, 3.62% 1,2-vinyl and Mn of 8.8 × 10 4 , Mw / Mn is 3.2.
[0102] Example 7 (different type of co-catalyst used from Example 1)
[0103] 1. Preparation of rare earth catalysts
[0104] (1) Preparation of CFA-1: Same as Example 1
[0105] (2) Preparation of Co-CFA-1:
[0106] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0107] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the gas was replaced with nitrogen three times, and then vacuumed. First, 1.2 mL (1.5 mol / L) of triisobutylaluminum toluene solution was added, and then 0.3 ml (1.5 mol / L) of methylaluminoxane toluene solution was added for activation. The mixture was activated at 25°C for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 154:1.
[0108] 2. Synthetic polydiene rubber
[0109] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0110] The yield of polybutadiene rubber was 85.4% by gravimetric determination, with stereoselectivity of 92.7% 1,4-cis, 4.31% 1,4-trans, 2.99% 1,2-vinyl and Mn of 6.7 × 10 4 , Mw / Mn is 3.6.
[0111] Example 8 (different type of co-catalyst used from Example 1)
[0112] 1. Preparation of rare earth catalysts
[0113] (1) Preparation of CFA-1: Same as Example 1
[0114] (2) Preparation of Co-CFA-1:
[0115] Weigh 1.64g of cobalt (II) acetate tetrahydrate in a 100mL beaker, use a measuring cylinder to measure 40mL of N-methylformamide (NMF) solution in the above beaker, and ultrasonically dissolve. Then weigh 0.1g of CFA-1 in the above solution, ultrasonically dissolve; react at 60°C for 24 hours. After the reaction is completed, the purple precipitate is filtered out, washed with hot NMF until the filtrate is completely colorless, then washed with methanol, and then vacuum dried at 250°C for 24h to obtain Co-CFA-1, and the mass percentage of Co in it is calculated by EDS content to be 13.88%.
[0116] (3) After cleaning and high-temperature baking to remove moisture, 6.2 mg Co-CFA-1 was added to the three-necked reaction bottle, and the mixture was replaced with nitrogen three times. Then, vacuum was drawn, and 1.2 mL of a toluene solution (1.5 mol / L) of ethylaluminum dichloride was first added, followed by 0.3 ml (1.5 mol / L) of a toluene solution of methylaluminoxane for activation. The mixture was activated at 25° C. for 20 min to obtain a butadiene polymerization catalyst based on Co-CFA-1, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 was 154:1.
[0117] 2. Synthetic polydiene rubber
[0118] A toluene solution of toluene and 1,3-butadiene (7.26 mL, 23.33 mmol 1,3-butadiene) was injected into the three-necked flask containing the Co-CFA-1-based butadiene polymerization catalyst, wherein the molar ratio of cobalt element to 1,3-butadiene was 6.2×10 -4 , stirred at 21°C for 2.5 hours. After the reaction was completed, the mixture was quenched with a 2,6-tert-butyl / ethanol solution (3 mL) with a volume ratio of 2,6-tert-butyl to ethanol of 1:100 for 5 minutes. The precipitate was washed with ethanol (30 mL), and the solid was vacuum dried at 55°C for 12 hours to obtain polybutadiene rubber.
[0119] The yield of polybutadiene rubber was 87.1% by gravimetric determination, with stereoselectivity of 86.7% 1,4-cis, 8.8% 1,4-trans, 4.5% 1,2-vinyl and Mn of 1.2 × 10 4 , Mw / Mn is 3.8.
Claims
1. A butadiene polymerization catalyst based on Co-CFA-1, characterized in that: The butadiene polymerization catalyst comprises Co-CFA-1, a co-catalyst and a toluene solvent, wherein the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 is 20 to 300:1; The Co-CFA-1 is prepared by the following method: heating a NMF dispersion of CFA-1 and cobalt acetate tetrahydrate at 55-65° C. for 18-30 hours, filtering, washing, and vacuum drying to obtain Co-CFA-1; The co-catalyst is composed of alkyl aluminum and methyl aluminoxane in a molar ratio of 2 to 5:1, and the alkyl aluminum is selected from at least one of diethyl aluminum monochloride, triisobutyl aluminum and ethyl aluminum dichloride.
2. The butadiene polymerization catalyst based on Co-CFA-1 according to claim 1, characterized in that: The feed mass ratio of the CFA-1 to the cobalt acetate tetrahydrate is 0.06-0.12:1.2-1.8; more preferably 0.07-0.10:1.3-1.
7.
3. The butadiene polymerization catalyst based on Co-CFA-1 according to claim 1, characterized in that: The molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 is 100 to 300:1, more preferably 150 to 160:
1.
4. The butadiene polymerization catalyst based on Co-CFA-1 according to claim 1, characterized in that: In the co-catalyst, the molar ratio of alkyl aluminum to methyl aluminoxane is 4:
1.
5. The butadiene polymerization catalyst based on Co-CFA-1 according to claim 1, characterized in that: In the butadiene polymerization catalyst, the molar ratio of the aluminum element in the co-catalyst to the cobalt element in Co-CFA-1 is 150-160:1; the co-catalyst is composed of diethylaluminum monochloride and methylaluminoxane, and the molar ratio of diethylaluminum monochloride to methylaluminoxane is 4:
1.
6. A method for preparing a butadiene polymerization catalyst based on Co-CFA-1 according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) heating a NMF solution of CFA-1 and cobalt acetate tetrahydrate at 55-65° C. for 18-24 hours, filtering, washing, and vacuum drying to obtain Co-CFA-1; (2) Add Co-CFA-1 to a clean, dry reaction vessel, first add a toluene solution of alkyl aluminum, then add a toluene solution of methylaluminoxane, and activate at 20 to 40° C. for 10 to 40 minutes to obtain a butadiene polymerization catalyst based on Co-CFA-1.
7. The preparation method according to claim 6, characterized in that: Step (2) is carried out under vacuum conditions, and the activation conditions are: activation at 20-25° C. for 20-30 min.
8. Use of the butadiene polymerization catalyst based on Co-CFA-1 as claimed in any one of claims 1 to 5 in the preparation of cis-polybutadiene.
9. The use according to claim 8, characterized in that: The application is specifically as follows: 1,3-butadiene monomer and a butadiene polymerization catalyst based on Co-CFA-1 are mixed in a solvent, and then a polymerization reaction is carried out to generate cis-polybutadiene, and the reaction process is carried out under vacuum conditions.
10. The use according to claim 9, characterized in that: The solvent is toluene.
Citation Information
Patent Citations
COMPOSITIONS AND METHODS FOR SELECTIVE olefin OLIGOMERIZATION COMPRISING METAL ORGANIC FRAMEWORKS
CN108025286A
Catalyst composition for polymerizing conjugated diene monomer
US20140378620A1
Process for the preparation of (CO) polymers of conjugated dienes in the presence of a catalytic system comprising a bis-imino-pyridine complex of cobalt
US20150329654A1
Compositions and methods for selective olefin oligomerization comprising metal organic frameworks
US20180250664A1